District-level forecast of northeast monsoon rainfall over Tamilnadu using Indian Ocean dipole mode index - SINGH, O.P.; PRASAD, ONKARI (MAUSAM, 2011)
The northeast monsoon season (October-December) contributes a substantial percentage of annual rainfall over Tamilnadu. The present paper describes a method for prediction of northeast monsoon rainfall (NEMR) over Tamilnadu on smaller spatial scale, i.e., district-level with sufficient lead time. Tamilnadu has been divided into ten homogeneous clusters of districts and the predictions are made for each cluster with lead times of two and one months using Indian Ocean dipole mode (IODM) index. A stronger western pole of IODM during August-September is associated with enhanced northeast monsoon activity over most of the districts of Tamilnadu. The predictions on the basis of regressions developed from NEMR and IODM index data have been validated for six years from 1997-2002. For many districts the mean errors between actual (realized) and predicted rainfall are within ±10%. Hence, using IODM index, it is possible to predict the NEMR activity over most of the districts of Tamilnadu with a lead time of two months, with only exception of NEMR over Kanyakumari which is not significantly correlated to IODM phenomenon.